(untitled) (Journal of Informatics and Mathematical Sciences, 2014)
A total domination polynomial of a graph G of order n is the polynomial D_td(G,x) =^n_t=γ_td(G)d_td(G,t)x^t, where d_td(G,t) is the number of total dominating sets of G of cardinality t. In this paper, we present various properties of total domination polynomial of graph G. Also determine the total domination polynomial of some graph operations.